(untitled) (Research, Society and Development, 2022)
Due to the constant contact with the earth, many agricultural machineries that have diesel engines, have problems in their performance due to the entry of dust particles in the air intake system. This work aimed to carry out a systematic review of the literature regarding the use of sensors in solving contamination problems in the air intake system in diesel engines. The inclusion criteria were articles that were complete and available, in English and Portuguese, and that had some application regarding the use of sensors in diesel engines, or that dealt with problems in air intake. The exclusion criteria, on the other hand, were the works that did not fit these eligibility criteria. Approximately 2,414 articles were retrieved, of which 31 met the eligibility criteria and were accepted for full reading. Given the limitations of the research, such as the reduced number of databases used, restriction of the language of the works, a meta-analysis was not possible to be conducted, limiting the research to only qualitative analyses. However, it was possible to notice some gaps in knowledge regarding the lack of works aimed at solving the problem raised, as well as the lack of works related to the theme at the national level.